Analysis on Role of Business Correspondents in Promoting Adoption of Mobile Banking in India: Examining the impact of business correspondents on mobile banking adoption in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The merging of media transmission and finance related management has made open doors for the rise of mobile managing account arrangements. Mobile managing an account offers gigantic open doors for banks in India to offer creative, area freethinker benefits on at whatever time, anyplace premise to existing customer as well as pull in both high esteem customer on one side and under-saved finance and unbanked customer at the other. Banks have contributed generously on building innovation and framework for conveyance of portable managing an account benefits in the course of the most recent decade however they are confronted with low client reception of mobile saving finance management undermining the immense potential it offers as far as decreased exchange costs and expanded infiltration of saving finance management bringing about higher gainfulness. This paper analysis on role of business correspondents in promoting adoption of mobile banking in India